Representation of non-verbal behavior in areal phrazeology of the ukrainian language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2018)
The article deals with the peculiarities of non-verbal behavior of Ukrainians, represented by regional idioms. Profound investigating of the systematic idiom organization and operation is impossible without taking into account the detailed descriptions of both the literary language and dialects. The phraseology description of a certain region makes it possible to form relatively holistic representations of individual fragments of the phraseological system, the correlation of common and dialectal phraseology, its dynamics and innovative processes. This research is focused on the set expressions, which are not recorded in dictionaries, or modified ones. The subject of the study is the dialectal phraseology of the southeastern dialect. On the basis of regional speaking practice, the knowledge of non-verbal communication components and the peculiarities of interpersonal interaction are revealed. It is determined that non-verbal protoword signs form the basis of human speaking. With the advent of verbal language, they do not disappear altogether, but go deep into the individual linguistic consciousness, representing the important elements of national culture, character, social interactions, traditions, etc. This paper describes the structural and semantic models of idioms related to the concept of “non-verbal behavior”, especially those ones related to body movements, posture, motion, gestures, facial expressions, peculiarities of the eye-sight. Investigating the structural and semantic features of the analyzed set expressions allows reconstructing the meaning of prototype communication situations in the Ukrainian dialectal linguistic environment.
Keywords: southeast dialect; dialect idiom; non-verbal behavior; gesture; facial expression; vision